B/P/N/O co-doped hierarchical porous carbon nanofiber self-standing film with high volumetric and gravimetric capacitance performances for aqueous supercapacitors. (20th March 2020) - Ma, Yongjun; Zhang, Xugang; Liang, Zhuo; Wang, Chenlong; Sui, Yan; Zheng, Bing; Ye, Yuncheng; Ma, Weijing; Zhao, Qi; Qin, Chuanli
Abstract: It is very challenging for carbon materials to gain high volumetric capacitance ( C v ) without sacrificing gravimetric capacitance ( C g ) as well as high rate and cycling performances to meet requirements for supercapacitors with limited space. Here, B/P/N/O co-doped hierarchical porous carbon nanofiber self-standing film was fabricated by a facile electrospinning and one-step carbonization/activation method using polyacrylonitrile solution containing boric acid and phosphoric acid. The optimized BPNOCNF-45 has high content (24.65 at.%) of heteroatoms, especially the highest content (12.93 at.%) of active heteroatom species (N-5, N-6, B–C, O–I, P2 and P3), high bulk density (1.19 g cm −3 ), high meso-/macropore ratio (70%), low charge transfer and ion diffusion resistance. These contribute to its prominent C v (395 F cm −3 at 1 A g −1 ) while maintaining high C g (332 F g −1 ) and excellent rate performance in KOH electrolyte. By comparison, the assembled symmetric supercapacitor in Na2 SO4 electrolyte delivers remarkably higher volumetric/gravimetric energy densities (21.1 Wh L −1 at 523.5 W L −1, 17.7 Wh kg −1 at 439.9 W kg −1 ) and capacitance retention of 90% after 10000 cycles. Furthermore, the assembled flexible supercapacitor also shows excellent capacitance performances. Such a densely co-doped porous carbon nanofiber film has great potential for applications in compact and miniaturized supercapacitors. Graphical abstract: Image 1 Highlights: Functional molecules were used to prepare B/P/N/O co-doped carbon nanofiber film. It displays high active heteroatom content, high meso/macropore ratio and bulk density. It exhibits prominent volumetric capacitance and high gravimetric capacitance. Symmetrical and flexible supercapacitors show excellent energy storage performances.